Autopsy Insights into Neck Structure Injuries in Hanging: A Forensic Perspective - Ramesh K. Gadhari; Madhusudan R. Petkar; Ajay N. Keoliya; Ajit G. Pathak; Narendra B. Kumar; Chaitanya V. Tingne (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Violent asphyxial deaths, like hanging, make up a signi𿿿cant portionof unnatural deaths globally. Despite being most frequently used for suicide, hangings in homicides or accidents are nonetheless uncommon. Aim: This study aimed to analyze neck structural injuries in hanging-related deaths through autopsy𿿿ndings, explicitly focusing on soft tissue injuries, fractures of the yoid bone and thyroidcartilage, and the correlation with age and gender. Methodology: Over the course of three years, a prospective analysis of 249 hangingrelated deaths through medicolegal autopsy was carried out in a tertiary healthcare facility in Maharashtra. The study excluded decomposed bodies and those with ambiguous causes of death. Results: The results revealed that 71.49% of victims were male, with a mean age of 31.75 years, and the most common ligature materials included dupatta, rope, and saree. Among the examined neck structures, soft tissue hemorrhage occurred in 6.83% of cases, and fractures were observed in 8.03%, with hyoid bone and thyroid cartilage fractures being the most frequent. Fractures were signi𿿿cantly ore common in victims aged 40 years or older (21.67%) compared to those under 40 years (3.7%) (p = 0.0001). No cases of cricoid cartilage fractures were identi𿿿ed. While neck structure fractures occurred slightly more frequently in males (8.43%) than in females (7.04%), this difference was not statistically signi𿿿cant. Conclusion: This study highlights the complex interplay of physical, psychological, and cultural factors in hanging deaths, with a particular focus on the vulnerability of young males. It emphasizes the need for targeted mental health care, thorough autopsy protocols, and further research into the impact of age-related anatomical changes and socioeconomic inÁuences on these tragic events.